Hyperthermic intraperitoneal chemotherapy (HIPEC) and neoadjuvant chemotherapy as prophylaxis of peritoneal carcinosis from advanced gastric cancer—effects on overall and disease free survival - Coccolini, Federico (J Gastrointest Oncol, 2016)
BACKGROUND: The possibility to enlarge criteria for intra-peritoneal chemotherapy (IPC) to all patients at high-risk to develop peritoneal carcinosis (i.e., with serosal invasion) is still discussed. METHODS: Retrospective case-control study. Three-groups: advanced-gastric-cancer (AGC) (pT4) without proven carcinosis: prophylactic group (PG), those with PC: treatment group (TG), AGC (pT3–pT4) operated without hyperthermic intraperitoneal chemotherapy (HIPEC), surgery alone group (SG T3, SG T4). RESULTS: Forty four patients. 26 (59.1%) were male. Sixteen (36%) patients underwent 16 HIPEC: 6 (38%) had AGC (pT4) without PC (PG), 10 (62%) had carcinosis (TG), 28 were operated without HIPEC (SG T3, SG T4). The mean disease free survival (DFS): TG: 7.7 months, SG T4: 21.6 months, SG T3: 27.7 months, PG: 34.5 months. DFS was significantly different for TG (P=0.03, P=0.021, P=0.013 respectively). The mean OS TG: 10 months, SG T4: 27.1 months, SG T3: 28.2 months, PG: 34.6 months. OS was significantly different for TG (P=0.04, P=0.04, P=0.045 respectively). Severe complication rate: TG: 60%, PG: 16.7%, SG T3: 7.7% and SG T4: 25% (P=0.035). Length-of-stay differs significantly (P=0.003); overall length-of-stay: 19.41 days [standard deviation (SD) ±15.03]; TG: 33.01 (SD ±23.08), PG: 20.17 (SD ±6.21), SG T3: 11.33 (SD ±3.22), SG T4: 15.36 (SD ±5.48). CONCLUSIONS: Prophylactic intraperitoneal chemotherapy associated to neoadjuvant chemotherapy increases the DFS and OS in patients with AGC without carcinosis. More data are needed in order to confirm these results.